Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Tenun Ikat di Sanggar Bliran Sina Watublapi Maumere - Andrik Nong Aven; Yoseph Darius P. Rangga; Yosef Tonce (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research addressed the purchasing decisions of Ikat weaving at Bliran Sina Workshop in Watublapi, Maumere, focusing on the influence of price and product quality. The objectives were twofold: (1) to assess the current landscape of price, product quality, and purchasing decisions in the local market, and (2) to analyze the individual and combined effects of price and product quality on these purchasing decisions.The research population comprised residents of Maumere town, with purposive sampling employed due to the infinite population size. Data were gathered through questionnaires and analyzed using descriptive and inferential statistics, particularly multiple linear regression. Hypotheses were tested using the F-test and t-test.Descriptive analysis reveals that variables related to purchasing decisions, price, and product quality are rated positively. The statistical findings from the t-tests indicate that both price and product quality significantly influence purchasing decisions of Ikat weaving at Bliran Sina Workshop, Watublapi, Maumere. Furthermore, the F-test confirmed that collectively, all independent variables exerted a significant impact on these purchasing decisions. Additionally, the determination analysis underscores the explanatory power of both variables in understanding fluctuations in purchasing decisions of Ikat weaving at Bliran Sina Workshop, Watublapi, Maumere.